Enhancing Transparency and Efficiency in Startupreneur Development through Blockchain Enabled Digital Finance: Transparansi dan Efisiensi Pengembangan Startupreneur pada Keuangan Digital Berbasis Teknologi Blockchain - Andayani, Dwi; Muhamad, Jihad Fadel; Lutfiani, Ninda; Wahid, Wahyu Nur; Moyo, Kgomotso (ADI Publisher, 2025)
Blockchain technology has become a vital foundation in the transformation of digital financial systems, particularly in supporting the growth of startupreneurs whorequire fast, secure, and transparent financial access. This study aims to analyze howtheimplementation ofblockchain technology can enhance operational efficiency and financial transparency in the development of digital startup businesses. Using a qualitative approach through literature review and best practice analysis, the research reveals that blockchain enables decentralized transactions, minimizes intermediaries, and ensures high data integrity ultimately strengthening investor and consumer trust in the startupreneur ecosystem. The adoption of smart contracts, immutable records, and automated verification also contributes to accelerating financial processes and mitigating fraud risks. However, challenges such as regulatory complexity, digital infrastructure readiness, and data security concerns remain obstacles to widespread blockchain adoption. These findings affirm that blockchain holds significant potential in creating a more inclusive, efficient, and sustainable digital financial model, in line with Sustainable Development Goals (SDGs) points 8 and 9. Recommendations are provided for startupreneurs and stakeholders to strategically integrate this technology into digital business development.